Prevalence of Cytopenia in the General Population—A National Health and Nutrition Examination Survey Analysis - Alpert, Naomi; Rapp, Joseph L.; Mascarenhas, John; Scigliano, Eileen; Tremblay, Douglas; Marcellino, Bridget K.; Taioli, Emanuela (Frontiers in Oncology, 2020)
Background: Cytopenia, a reduced count of blood cells manifesting as anemia, neutropenia, and/or thrombocytopenia is frequently associated with other medical conditions. However, a cytopenia may not be accompanied by a known determinant, and in some of these cases, may be a precursor to pre-malignancies or hematologic cancers. Little is known about the prevalence of these unexplained cytopenias, and their distribution in the population. Materials and Methods: The National Health and Nutrition Examination Survey from 1999-2002 was used to identify those with a cytopenia in the general population. Those without an identifiable determinant in NHANES were classified as having unexplained cytopenia. Weighted frequencies were examined to assess the prevalence of unexplained cytopenia in the population. Distribution of blood counts comparing those with unexplained cytopenia and the general population were examined. Multivariable logistic regression was conducted to assess the association between unexplained cytopenia and demographic factors. Results: Of the 7962 people in the sample, 236 (2.0%) had any cytopenia and 86 (0.9%) had an unexplained cytopenia. Approximately 43% of all cytopenias were not accompanied by a clinical determinant. Unexplained cytopenia was more common in men (1.1%) than in women (0.7%), and in Non-Hispanic Black participants (3.4%). Among those with an unexplained cytopenia, the majority (74.8%) manifested as neutropenia. Compared to those with no cytopenia, those with unexplained cytopenia were significantly less likely to be female, have BMI ≥30 kg/m2, and to work in the service industry, and were significantly more likely to be non-Hispanic Black. Conclusions: This is the first study to examine the prevalence of unexplained cytopenia in a nationally representative sample and may serve as a baseline for comparison with other populations. Future research to identify risk factors for development of malignant hematological disorders among those with unexplained cytopenia is warranted.